Primary headache epidemiology in children and adolescents: a systematic review and meta-analysis - Onofri, Agnese; Pensato, Umberto; Rosignoli, Chiara; Wells-Gatnik, William; Stanyer, Emily; Ornello, Raffaele; Chen, Hui Zhou; De Santis, Federico; Torrente, Angelo; Mikulenka, Petr; Monte, Gabriele; Marschollek, Karol; et al. (The Journal of headaches and pain, 2023)
INTRODUCTION: Headache is the most prevalent neurological manifestation in adults and one of the leading causes of disability worldwide. In children and adolescents, headaches are arguably responsible for a remarkable impact on physical and psychological issues, yet high-quality evidence is scarce. MATERIAL AND METHODS: We searched cross-sectional and cohort studies in Embase, Medline, Web of Science, and Cochrane databases from January 1988 to June 2022 to identify the prevalence of headaches in 8-18 years old individuals. The risk of bias was examined with the Joanna Briggs Institute (JBI) scale. A random-effects model was used to estimate the pooled prevalence of pediatric headache. Subgroup analyses based on headache subtypes were also conducted. RESULTS: Out of 5,486 papers retrieved electronically, we identified 48 studies that fulfilled our inclusion criteria. The pooled prevalence of primary headaches was 11% for migraine overall [95%CI: 9-14%], 8% for migraine without aura (MwoA) [95%CI: 5-12%], 3% for migraine with aura (MwA) [95%CI:2-4%] and 17% for tension-type headache (TTH) [95% CI: 12-23%]. The pooled prevalence of overall primary headache in children and adolescents was 62% [95% CI: 53-70%], with prevalence in females and males of 38% [95% CI: 16-66%] and 27% [95% CI: 11-53%] respectively. After the removal of studies ranked as low-quality according to the JBI scale, prevalence rates were not substantially different. Epidemiological data on less common primary headaches, such as trigeminal autonomic cephalalgias, were lacking. CONCLUSION: We found an overall remarkably high prevalence of primary headaches in children and adolescents, even if flawed by a high degree of heterogeneity. Further up-to-date studies are warranted to complete the picture of pediatric headache-related burden to enhance specific public interventions.
Keywords: dospělí; migréna bez aury; Female; Prevalence; dítě; Migraine with Aura; migréna s aurou; Adult; ženské pohlaví; průřezové studie; Tension-Type Headache; Adolescent; lidé; bolesti hlavy; Migraine without Aura; prevalence; Cross-Sectional Studies; Male; Headache; tenzní bolesti hlavy; Child; mužské pohlaví; mladiství; Humans